Real-time monitoring of mercury(II) in water and food samples using a quinoline-based ionic probe. (1st May 2023) - Che, Siying; Yin, Linlin; Chen, Ming; Fan, Yao; Xu, Anni; Zhou, Chunsong; Fu, Haiyan; She, Yuanbin
Graphical abstract: Highlights: Ionic liquids exhibited simultaneously fluorescent and semicolorimetric signals. The probe improved sensitivity to mercury(II) through electrostatic attraction. The probe could be applied to detection mercury(II) in complex real samples. Abstract: Herein, a novel ionic fluorescent probe for mercury(II) detection is presented consisting of a functional quinoline-based IL. Interestingly, the probe displayed high sensitivity (0.8 nM) and selectivity through the regulation function of electrostatic attraction, where its performance was significantly superior to that of quinoline probes without negative charge. Furthermore, the probe was found to exhibit two different fluorescent signals and colorimetric signals in the presence of different concentrations of mercury(II), which was consistent with the reaction mechanisms of the generation of large conjugated systems and the formation of anion-mercury(II) complexes. Moreover, this probe could be further loaded on a simple filter paper to serve as a visual paper sensor due to its adequate response time of less than 5 s. This regulation function strategy of electrostatic attraction has excellent potential for use in the precise detection of targeted analytes in real complex samples with improved accuracy and selectivity.